Thermoelectric measurement of a single, TiO₂-catalyzed Bi₂Te₃ nanowire - Moosavi, H; Kojda, D; Kockert, M; Schoenherr, P; Hesjedal, T; Fischer, S; Kroener, M; Woias, P (MDPI, 2017)
We report on the functionality of our Thermoelectric Nanowire Characterization Platform (TNCP). As a proof of concept of our design, we present a set of experimental results obtained from the characterization of a single Bi2Te3 nanowire, allowing for the determination of the nanowire’s electrical conductivity and Seebeck coefficient.